(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
In the current research the effect of wind load on structural stability of building structure is evaluate using techniques of Computational Fluid Dynamics. The CFD analysis on building is conducted using ANSYS simulation package. The FSI simulations considered the complex interactions between the structural components and the surrounding fluid flow, providing valuable insights into the structural response and its vulnerability to external loading conditions. Through a combination of computational tools and numerical methods, the study was able to accurately predict the structural response, including deformations, stresses, and critical failure points.